2022
DOI: 10.1111/zph.12955
|View full text |Cite
|
Sign up to set email alerts
|

Spoligotype analysis of Mycobacterium bovis isolates from cattle and assessment of zoonotic TB transmission among individuals working in bovine TB‐infected dairy farms in Ethiopia

Abstract: Bovine tuberculosis (bTB) is a disease with impact on dairy productivity, as well as having the potential for zoonotic transmission. Understanding the genetic diversity of the disease agent Mycobacterium bovis is important for identifying its routes of transmission. Here we investigated the level of genetic diversity of M. bovis isolates and assessed the zoonotic potential in risk groups of people working in bTB‐infected dairy farms in central Ethiopia. M. bovis was isolated and spoligotyped from tissue lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Few studies investigated whether farmers knew that raw milk and dairy (Africa n=8; Asia n=2) or raw meat (Africa n=6) consumption could result in zoonotic infection with bTB (28, 30, 31, 33, 44, 62). Except for the farmer populations investigated by Kazoora et al (44), most studies found this knowledge was prevalent among less than 30% of the farmers interviewed.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies investigated whether farmers knew that raw milk and dairy (Africa n=8; Asia n=2) or raw meat (Africa n=6) consumption could result in zoonotic infection with bTB (28, 30, 31, 33, 44, 62). Except for the farmer populations investigated by Kazoora et al (44), most studies found this knowledge was prevalent among less than 30% of the farmers interviewed.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the genetic diversity of M. bovis is necessary for detecting its routes of transmission. 135 Single nucleotide polymorphism (SNP) analysis within virulence genes, which appear with the highest number of SNPs, indicated that M. bovis was continuously modifying and adapting specific mechanisms to sustain dissemination among environments and different hosts. 136 The identification of non-synonymous SNPs on the virulence genes allowed for the differentiation of various groups.…”
Section: Wgs Insights Into the Genetic Diversity Of M Bovismentioning
confidence: 99%